Community empowerment to stop smoking at selected villages in Hambantota, Sri Lanka - Nisansala Gamage (Tobacco Induced Diseases, 2018)
Background and challenges to implementation Tobacco smoking is the cause of many preventable diseases in the world. According to the WHO tobacco kills up to half of its users. Sri Lanka as a middle income country, tobacco smoking is one of the biggest economic threats especially in rural settings. The intervention was carried out with the intention to reduced smoking among villages. ADIC implemented the intervention in collaboration with Women Development Federation, Hambantota (WDF) which is the largest women organization in Sri Lanka by mobilizing women voice against violence related drugs and women rights.